PENGELOLAAN PROGRAM YANG BERDAMPAK POSITIF PADA MURID (PENGALAMAN PRAKTIS PENDIDIKAN GURU PENGGERAK) - Riswakhyuningsih, Tri; Susiati, Eva; i, Wulandari; Duryat; Khusnul Fatekhah, Helmi; Kumariyah (Bapelitbang Kabupaten Batang, 2025)
Program management that has a positive impact on students is the 10th module of 10 modules studied in the education of teacher movers. The purpose of the study is to share learning experiences of program management that has a positive impact on students. The study was conducted using a qualitative descriptive method. Data sources include program management modules that have a positive impact on students, independent assignments, group assignments, and reflection journals. Data were collected by reviewing modules, exploring the Learning Management System, and documentation. Data analysis was carried out using triangulation techniques. Learning activities use the flow: starting from oneself, concept exploration, collaboration space, contextual meaning, elaboration of understanding, connections between materials, and real action. Starting from oneself, reflecting on their past learning experiences. Concept exploration, through reading, discussion, and reflection activities, and constructing understanding. Collaboration space, creating and presenting examples of programs that promote student leadership. Contextual demonstration, creating a program plan that utilizes the BAGJA change management model. Elaboration of understanding, discussion and Q&A with instructors related to learning programs that foster student leadership. Connections between materials, creating a synthesis of understanding about school programs that have an impact on students. Real action, implementing stages B&A based on the BAGJA change initiative model. Keywords: Leading Teachers, Positive Impact, Students, Program Management